Laju Reaksi Penghilangan Fosfat pada Limbah Cair Artifisial NPK Menggunakan Sistem Floating Treatment Wetlands - Sugiarti; Nurul Setiadewi; Cynthia Henny; Dewi Verawati; Agus Waluyo (Universitas Andalas, 2023)
Floating Treatment Wetland (FTW) is a form of wetland that functions to remove waste such as Nitrogen (N element) and Phosphorus (Phosphorous/P element) waste by utilizing plant roots as pollutant absorbers. This study aims to examine the reaction rate of phosphate removal from synthetic P waste through FTW. The water plants used were water jasmine (Echinodorus palifolius) and banana (Helliconia psittaforum). Four FTW ponds are filled with synthetic P waste. The first pond is a control pond, while the second pond is filled with FTW without plants, and the third and fourth ponds are filled with each of the aquatic plants mentioned above. The study was conducted from July to mid-August 2019. Water samples were taken in four pools five times in the first week, three times in the second week and twice in the third to sixth weeks. The parameters measured are water temperature, pH, Oxidative Reductive Potential (ORP) and phosphate. The data analysis carried out was calculating the phosphate reaction rate for each measured sample. The rate of phosphate decreases in proportion to the decrease in phosphate concentration in the test pond. Aquatic plants have been proven to remove phosphate from synthetic waste by using it as a nutrient for plant growth.